Feed resources and nutritional management of dairy herds in urban and peri-urban dairy production systems in Ethiopia - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N. (Ethiopian Society of Animal Production, 2000)
This study was carried out to assess feed resources and nutritional management of dairy cows in market oriented urban and peri-urban dairy production systems in and around Addis Ababa between September-November, 1998. Three sub dairy production systems, i.e. intra-urban, large peri urban and urban farms in secondary towns, constituted the study proper. A total of 41 farms (15 from intra-urban, 6 from large peri-urban and 20 from secondary towns) were used. Structured questionnaires were developed and cross-sectional survey was implemented. Twenty-three different feed types were identified and categorized in to five classes: pasture/roadside grazing, hay, crop residues, concentrate sand non-conventional feeds. Grazing roadside is practiced by 6.7% of the intra-urban while grazing pasture is limited to 33% of the large peri-urban dairy farms. Hay is utilized by all production sub systems except for 40% of secondary town dairy farms. However, crop residue is solely utilized by the dairy farms in secondary towns. Green feed (grass) is used across all the production sub-systems. Home mixed concentrates using fourmill by-products and/or oilseed cakes dominate the systems. Among non-conventional feeds, Atella (traditional brewery and liquor residue) and pulse hulls are utilized by 80% and 47% of the intra-urban farms, respectively. About 85% of the farms in intra urban and secondary towns use Atella and pulse hulls. Common salt is used in all farms; however, the use of commercial mineral lick is non-existent. Feeding systems of calves, heifers and cows varied considerably between and within the production sub-systems. Green feeds, vegetable waste, hay and crop residues are the major feed resources during the rainy season as compared to the use of hay and crop residues in dry season. Atella is used as a complement diet throughout the year. Atella has high crude protein (20%)) and Organic matter (97%) content. The crude protein content of pulse hulls ranged from 9% to 16% In conclusion, the heavy reliance on the use of purchased conserved feeds and agro-industrial by products coupled with high-grade dairy stock indicates that urban and peri urban dairying is an intensified form of livestock production system. Capital and land problems force intra-urban and secondary towns farms to use diverse assortment of feed,types, which fluctuate seasonally. Besides, supplementation of low quality roughage with non-conventional feeds is an important feeding strategy. Furthermore, lack of mineral supplementation and absence of appropriate feeding system in hay and crop residue based system may impair the reproductive and productive performance of grade dairy cows, calling for further research on the quantity and quality of the available feed resources, their utilization and impact on the performance of dairy herd.